Edible economics : a hungry economist explains the world - Chang, Ha-Joon (Public Affairs, 2023)
Bestselling author and economist Ha-Joon Chang makes challenging economic ideas delicious by plating them alongside stories about food from around the world, using the diverse histories behind familiar food items to explore economic theory. For Chang, chocolate is a lifelong addiction, but more exciting are the insights it offers into postindustrial knowledge economies; and while okra makes Southern gumbo heart-meltingly smooth, it also speaks of capitalism's entangled relationship with freedom.